Wali Allah menurut al-Hakim al-Tirmidzi dan Ibnu Taimiyyah - Lilik Mursito (Universitas Darussalam Gontor, 2015)
The discussion about wali presented in the early time on the hand of al-Hakim al Tirmidzi, which reaps number of responses from Muslim scholar because of his misleading. One of them is Ibn Taimiyyah. Al-Hakim and Ibn Taymiyyah have their own view about wali with several distinctions. In the definition of wali, al-Hakim al-Tirmidzi used more general language than Ibn Taimiyyah, as well as characteristics, how to be wali, the classification, concept of karamah, and the concept of khatm al-awliya’. According to writer, al-Hakim al-Tirmidzi’s view about wali able to deepen our understanding about Sufism, meanwhile Ibn Taimiyyah’s view will led us to comprehend Sufism from modernist point of view. This paper conclude that: both of figures seen that wali of Allah are the servants submissive and obedient in running His command; according to al-Hakim al Tirmidzi, degree of wali can be reached purely from Allah’s bounty and the effort of servants themselves, while Ibn Taimiyyah seen that the degree could be reached in the way of faith and piety of the servant; al-Hakim al-Tirmidzi seen that karamah is the most urgent for wali, while Ibn Taimiyyah did not; al-Hakim al-Tirmidzi utilized the quality of deeds to measure the best people and purity of heart to measure the best wali, while Ibn Taymiyyah utilized the quality of deeds as the assessment standard to measure best people and wali.